The Legal Character of Mining Service Contracts by State-Owned Enterprises/SOEs (Persero) in Indonesia - Umar, Wahyudi; Hernoko, Agus Yudha; Anand, Ghansham; Anggriawan, Rizaldy (Faculty of Law, Universitas Pattimura, 2026)
Introduction: Mining service contracts executed by State-Owned Enterprises (SOEs) in the form of persero play a strategic role in Indonesia’s natural resource governance. Although formally framed as commercial contracts, these agreements involve public assets, state authority, and environmental responsibilities, creating legal complexities that challenge traditional private contract doctrines.Purposes of the Research: This article aims to examine the legal character of mining service contracts entered by Indonesian SOEs persero and to determine whether such contracts can be classified as purely private commercial agreements or should be understood as contracts with inherent public dimensions.Methods of the Research: This study employs normative legal research using statutory, and conceptual approaches. Legal materials are examined through document analysis of legislation, doctrinal writings, and relevant legal principles governing contracts, state owned enterprises persero, and mineral and coal mining activities.Results / Main Findings / Novelty/Originality of the Research: The study finds that mining service contracts by SOEs cannot be categorized as ordinary private contracts. Instead, they constitute public–commercial contracts characterized by limited contractual freedom, heightened public accountability, and embedded state obligations. This conceptualization offers a refined legal framework for understanding SOE contracts in strategic sectors.